2006
DOI: 10.1097/01.wnf.0000236768.54150.8c
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of First-choice Topiramate Therapy in Newly Diagnosed Infantile Spasms

Abstract: Topiramate proves to be an effective and safe first-choice drug not only as adjunctive but also as monotherapy of infantile spasms in children younger than 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
(28 reference statements)
1
9
0
Order By: Relevance
“…The mean dosage of TPM applied in our study was relatively low compared with other reports conducted with the low dosages18,26,27) as well as high14). There was a study, however, which concluded that the mean dosage during stabilization was 5.2 mg/kg/day similar to that of our study17). In the other study30), a wide range of TPM dosage (ranges from 1.3 to 35 mg/kg/day) was reported and some patients who responded in 1 month or less did so at very low doses, 1.3 and 3.4 mg/kg/day.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The mean dosage of TPM applied in our study was relatively low compared with other reports conducted with the low dosages18,26,27) as well as high14). There was a study, however, which concluded that the mean dosage during stabilization was 5.2 mg/kg/day similar to that of our study17). In the other study30), a wide range of TPM dosage (ranges from 1.3 to 35 mg/kg/day) was reported and some patients who responded in 1 month or less did so at very low doses, 1.3 and 3.4 mg/kg/day.…”
Section: Discussionsupporting
confidence: 77%
“…Other studies have treated patients with multiple antiepileptic drugs concurrently with TPM17). But only a few studies suggested that TPM can be a first-line drug and can be used as monotherapy18,19).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of limited options with significant toxicity, researchers have actively investigated second‐generation anticonvulsants possessing relatively fewer side effects, including felbamate (Hosain et al, 1997), levetiracetam (Lawlor & Devlin, 2005), topiramate (Hosain et al, 2006; Zou et al, 2006), and zonisamide (Lotze & Wilfong, 2004). However, none of these drugs have demonstrated spasm‐free outcomes similar to ACTH, and often have been used primarily for refractory spasms (Mackay et al, 2004).…”
mentioning
confidence: 99%
“…TPM has been very effective in treating childhood forms of epilepsy, including Lennox–Gastaut syndrome, juvenile myoclonic epilepsy (Mikaeloff et al 2003; Glauser et al 2007; Malphrus and Wilfong 2007), infantile spasms (Valencia et al 2005; Zou et al 2006), and West syndrome (Korinthenberg and Schreiner 2007). Generally, it has been well tolerated in children, and doses on a mg‐per‐kg body weight basis have often exceeded those of adults (Valencia et al 2005; Zou et al 2006; Glouser et al 2007), possibly because of a more rapid elimination rate in children than in adults (Adin et al 2004). TPM is approved for therapy in children as young as 2 years of age, but some clinical studies in younger children have been described (Valencia et al 2005; Zou et al 2006).…”
Section: Pharmacodynamics Related To Adverse Clinical Effectsmentioning
confidence: 99%